Efektivitas Pembelajaran Kitab Taisirul Kholaq Dalam Meningkatkan Akhlak Siswa - Erisa Veriany Nur Annisa; Jumari Jumari (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2024)
Juvenile delinquency is an act of violating norms and rules committed during adolescence or the transition from childhood to adulthood. Teenagers are an asset that every country has. This research aims to find out; 1) Local Content Learning of Kitab Taisirul Kholaq at An-Nur Al Anwar Junior High School Bululawang Malang, 2) Student morals at An-Nur Al Anwar Junior High School Bululawang Malang, 3) The Effect of Local Content Learning of Kitab Taisirul Kholaq on Student Morals at An-Nur Al Anwar Junior High School Bululawang Malang. This research was conducted with a quantitative approach using the type of correlation research, used to determine the correlation or relationship of local content learning Kitab Taisirul Kholaq on student morals. The sample used in this study was 15% of the population with a purposive sampling technique of 54 students. Data collection techniques using observation, questionnaires, and documentation. The results showed 1) it is known that the minimum value of the local content variable is 36, the maximum value is 62, the mean is 44.13, Std Deviation is 4.434, Variance is 19.662 from 54 respondents. 2) The minimum value of the student morals variable is 46, the maximum value is 83, the mean is 62.07, Std Deviation is 6.375, Variance is 40.636 from 54 respondents. 3) There is an influence of local content learning of the book of Taisirul Kholaq on student morals at An-Nur Al Anwar Junior High School with a moderate level of strength.